THE PSYCHOLOGICAL-SOCIAL CLIMATE AND ITS RELATION TO SPORTS ACHIEVEMENT AMONG UNDER-20 ATHLETES IN SOME TRACK AND FIELD EVENTS - Hassan, Dr. Ali Bukheet (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The research aims to identify the level of psychological climate and achievement among athletes under 20 years old (both males and females) in some track and field events. It also aims to understand the correlation between psychological climate and sports achievement among young athletes under 20 years old (both males and females) according to their events. The researcher used the descriptive method with correlational studies, as it is suitable for achieving the research objectives. The study included 99 participants (62 males and 37 females) in events such as 100m hurdles for females, 110m hurdles for males, 800m run, long jump, and discus throw. Based on the research results, the following conclusions were made High levels of psychological climate among males and low levels among females, Increased needs negatively impact achievement levels, Lack of attention to educational, psychological, social, and health aspects by teachers and coaches.